Pengembangan Media Video Interaktif pada Kemampuan Bahasa Anak Usia Dini TK IB 71 Sialang Gaun - Oqtika, Yulia; Salahudin, Amar; Ningsih, Sri Yunimar (Universitas Batanghari Jambi, 2025)
Education is defined as a process related to human potential (ability, capacity) that is easily influenced by habits, which are then perfected with good habits, through media that are arranged and managed in such a way by humans to help others or themselves in achieving the goals set. In Indonesia itself, a 12-year compulsory education program has been implemented, starting with Kindergarten (TK), Elementary School (SD), Junior High School (SMP), and Senior High School (SMA). This shows that the early education taken by a person will be the basis for the emergence of positive social attitudes and growth regarding a knowledge competency. Character building and the formation of social attitudes that are easy to do when the child is still in Kindergarten The childhood growth period is the